Morphology, Multilocus Phylogeny, and Toxin Analysis Reveal Amanita albolimbata, the First Lethal Amanita Species From Benin, West Africa - Codjia, Jean Evans I.; Cai, Qing; Zhou, Sheng Wen; Luo, Hong; Ryberg, Martin; Yorou, Nourou S.; Yang, Zhu L. (Frontiers in Microbiology, 2020)
Many species of Amanita sect. Phalloideae (Fr.) Quél. cause death of people after consumption around the world. Amanita albolimbata, a new species of A. sect. Phalloideae from Benin is described here. The taxon represents the first lethal species of A. sect. Phalloideae known from Benin. Morphology and molecular phylogenetic analyses based on five genes (ITS, nrLSU, rpb2, tef1-α, and β-tubulin) revealed that A. albolimbata is a distinct species. The species is characterized by its smooth, white pileus sometimes covered by a patchy volval remnant, a bulbous stipe with a white limbate volva, broadly ellipsoid to ellipsoid, amyloid basidiospores, and abundant inflated cells in the volva. Screening for the most notorious toxins by LC-HRMS revealed the presence of α-amanitin, β-amanitin, and phallacidin in A. albolimbata.